MicroRNAs modulated by DPP-4 inhibitor and bedtime NPH insulin therapy in individuals with type 2 diabetes - Santos, Aritania Sousa; Bando, Silvia Yumi; Correa Giannella, Maria Lucia Cardillo; da Silva, Maria Elizabeth Rossi (Frontiers in Endocrinology, 2025)
BackgroundMicroRNAs (miRNAs) and their target genes can elucidate mechanisms of drug action and serve as potential therapeutic biomarkers.MethodsTo evaluate the effects of bedtime NPH insulin and sitagliptin on serum miRNA expression in individuals with type 2 diabetes (T2D), thirty-two patients with T2D inadequately controlled with metformin and glyburide were randomly assigned to an additional 6-month treatment with either bedtime NPH insulin or sitagliptin. Before and after treatments, fasting as postprandial (60, 120, and 180 minutes) concentrations of glucose, C-peptide, glucagon-like peptide 1 (GLP1), and triglycerides were measured. Fasting HbA1c was also assessed. Expression levels of selected miRNAs were analyzed using quantitative polymerase chain reaction.ResultsThe sitagliptin and bedtime NPH insulin groups were comparable in age, body mass index, diabetes duration, and baseline metabolic variables. Both treatments led to a similar reduction in HbA1c. Only sitagliptin increased postprandial GLP1 concentrations. Sitagliptin treatment upregulated six miRNAs: miR-24-3p, miR-27a-3p, miR92a-3p, let-7d-5p, miR-30c-5p, and miR-660-5p. NPH insulin upregulated four miRNAs: miR-92a-3p, miR-193b-3p, miR-320a-3p and miR-30c-5p. Both treatments increased miR-92a-3p and miR-30c-5p, particularly at fasting and 60 minutes post-meal. KEGG pathways analysis revealed enrichment in signaling pathways related to insulin action, growth/development, cellular senescence, lipid/atherosclerosis, Th17 cell differentiation, insulin resistance, autophagy, and apoptosis. Sitagliptin and bedtime NPH insulin induced metabolic improvement and distinct modulation of circulating miRNAs, with sitagliptin influencing a broader spectrum of miRNA expression.ConclusionThe upregulated miRNAs are involved in pathways related to insulin signaling, inflammation, and cellular homeostasis and support the hypothesis that sitagliptin exerts pleiotropic effects beyond glycemic control.